Technological Innovation and Competitiveness in The Global Economy: India's Changing Status and Its Implications - Mungila Hillemane, Bala Subrahmanya (School of Business and Management Institut Teknologi Bandung, 2013)
Â Â This paper probes the changing innovation status and resultant competitiveness in the context of global economy and questions the recent ranking improvements of India on the basis of hard economic facts. This paper has made use of secondary data comprising innovation indices and competitiveness rankings published by international organizations and reputed business schools from time to time since 1996 to analyze the changing status of India internationally. Later, using secondary data on key macro-economic variables published by the Government of India, the recent ranking of India is closely examined as well as recent steps taken by the government of India to improve competitiveness is elaborated. The study throws light on the changing but improving innovation dimensions and competitiveness ranking of India since 1996 till 2010. From nowhere India emerges and occupies the second slot, after China, in the global competitiveness ranking. But hard core macro-economic variables do not justify Indiaâ€™s elevation to the top in any way. Given this, the study throws light on the recent policy measures announced by the Government of India and its implications as well as policy imperatives.